2011
DOI: 10.1039/c1cp22284h
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and ion chemistry in low pressure dc plasmas of H2/N2 mixtures: routes for the efficient production of NH3 and NH4+

Abstract: The chemistry in low pressure (0.8-8 Pa) plasmas of H(2) + 10% N(2) mixtures has been experimentally investigated in a hollow cathode dc reactor using electrical probes for the estimation of electron temperatures and densities, and mass spectrometry to determine the concentration of ions and stable neutral species. The analysis of the measurements by means of a kinetic model has allowed the identification of the main physicochemical mechanisms responsible for the observed distributions of neutrals and ions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
259
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(278 citation statements)
references
References 74 publications
16
259
2
1
Order By: Relevance
“…Plasmas containing H 2 -N 2 are extensively applied for thin film growth and material processing on the nanometer scale [1][2][3] . For example, thin films of silicon nitride which are fabricated by plasma-enhanced chemical vapor deposition (PECVD) in the semiconductor industry are used as passivation layers 4 and in the photovoltaic industry 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas containing H 2 -N 2 are extensively applied for thin film growth and material processing on the nanometer scale [1][2][3] . For example, thin films of silicon nitride which are fabricated by plasma-enhanced chemical vapor deposition (PECVD) in the semiconductor industry are used as passivation layers 4 and in the photovoltaic industry 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar models applied to H 2 +D 2 , H 2 +N 2 and H 2 +Ar discharges can be found in refs. [37][38][39][40]. The model accounts for the main physico-chemical processes: electron impact dissociation and ionization, ion-molecule and ion-ion reactions, neutralization at the wall and heterogeneous chemistry.…”
Section: Modelmentioning
confidence: 99%
“…In the steady state, a small fraction of these hot atoms survives and can be detected either in the line profiles of Balmer emission lines of H atoms [81] or indirectly in the energy resolved mass spectra of H + and O + ions [81][82][83]. However, previous works carried out on this reactor for different gas mixtures at comparable pressures [33,34,[36][37][38][39] have shown that the assumption of a Maxwellian distribution is not a bad approximation for the global kinetics, and we have adopted it here for lack of better information on the actual eedf. The limitations of this approximation should be taken into account in the interpretation of the results.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations